2021
DOI: 10.1371/journal.pone.0257038
|View full text |Cite
|
Sign up to set email alerts
|

Fine tuning of the side-to-side tenorrhaphy: A biomechanical study assessing different side-to-side suture techniques in a porcine tendon model

Abstract: Recent studies conclude that a new technique for tendon transfers, the side-to-side tenorrhaphy by Fridén (FR) provides higher biomechanical stability than the established standard first described by Pulvertaft (PT). The aim of this study was to optimize side-to-side tenorrhaphies. We compared PT and FR tenorrhaphies as well as a potential improvement, termed Woven-Fridén tenorrhaphy (WF), with regard to biomechanical stability. Our results demonstrate superior biomechanical stability and lower bulk of FR and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Effective exposure during the tendon anastomosis is vital to ensuring a successful tendon repair. Some researchers have concluded that the strength and elasticity of the tendon anastomosis are equal to the size and volume of the sutures applied to it (Rawson et al, 2013; Wilhelm et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Effective exposure during the tendon anastomosis is vital to ensuring a successful tendon repair. Some researchers have concluded that the strength and elasticity of the tendon anastomosis are equal to the size and volume of the sutures applied to it (Rawson et al, 2013; Wilhelm et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In this study we established an in vitro model to objectively assess the stability of skin samples with or without various incision patterns. Similar models (including endpoints and clinimetrics) have been successfully used in the past, in particular, to assess the stability of tendon sutures and tenorrhaphies [14,29,30]. However, the findings of our study are significantly limited by its (in vitro) set-up.…”
Section: Discussionmentioning
confidence: 99%
“…Means and standard deviations were calculated for the different groups. Tensile testing was filmed using a Legria HF M31 video camera (Canon Co., Ltd., Ohta-ku, Tokyo, Japan) to document the mode of failure (pull-out vs. suture breakage) [14]. Considering the cost for acquisition and maintenance of the biomechanical testing equipment as well study-specific materials (skin samples, suture material, 3D-printed incision-pattern templates) the average cost per skin sample tested was approximately EUR 4.80.…”
Section: Biomechanical Testingmentioning
confidence: 99%
“…(2022) suggest that three is the optimal number, exact technical details) or a Friden weave or alternative (Graham et al., 2022; Pulvertaft, 1956). A knowledge of the literature comparing the various suture techniques will gain extra marks (for instance Bidic et al., 2009; Brown et al., 2010; Wilhelm et al., 2021). You will need to know what suture to use and how you are going to judge the tension of repair.…”
Section: Clinical Casementioning
confidence: 99%